Magnitude and Determinants of Computer Vision Syndrome (CVS) among IT Workers in Kathmandu, Nepal - Poudel, Sudip; Khanal, Shankar Prasad (Nepalese Journal of Ophthalmology, 2020)
Introduction: Computer Vision Syndrome (CVS) is developed among computer workers due to long time working with computers or viewing of the video display terminal (VDT). The objective of this study is to determine the magnitude and determinants of CVS symptoms among IT officers. Materials and methods: A cross sectional study of IT office workers was conducted at Kathmandu from March to April 2019. Self-administrated questionnaire and observation of researcher was applied to collect information. CVS defect was considered if the participants were having minimum of one symptom during /following use of VDT. The proportion of CVS and its association with different independent factors was carried out. Results: The prevalence of CVS reported by 263 participants was 82.5% (95% CI: 81.3% - 83.6%), of them 163(62.0%) were not aware about bad effects of computers to the visual apparatus. Goggles were used as protection against CVS by 140(53.2%) participants. CVS symptoms included headache 127(48.0%), tired eyes 123(47.0%) and eye strain 114(43.0%). Use of computer for more than 4.75 hours/day experienced CVS. The mean office work included 7.7 ± 2.02 hours computer work. The video display gadgets usage in home was 2.7 ± 2.35 hours/ day. Not taking breaks (OR:7.3; 95% CI:2.2 - 24.9), not massaging eyes (OR:7.5; 95% CI:1.2 - 47.7), unusual viewing distance (OR:9.0; 95% CI:2.0 - 44.5), improper posture (OR:3.6; 95% CI:1.3 - 10.3), computer usage for more than 10 hours/ day (OR:5.4; 95% CI:1.6 - 18.2) and not aware of CVS (OR:7.2; 95% CI:2.6 - 20.3) were significant predictors of CVS in IT workers. Conclusion: Most of the IT workers had CVS. Health education and care of IT workers based on predictors found need to be strengthened in the study area.